Penggunaan Google Classroom untuk Mendukung Perkuliahan di IAI-N Laa Roiba Bogor - Farah Chalida Hanoum; Dedi Junaedi; Mia Hermaliana; Siti Aminah (LPPM Institut Nasional Laa Roiba Bogor, 2019)
ABSTRACTThis study aims to analyze the potential and opportunities for the application of e-learningapplications at IAI-N Laa Roiba; explore differences in perceptions of student-lecturer status, gender,faculty, campus location, and age group in implementing Google Classroom as an e-learning model at IAINLaa Roiba. The research method used is a combination of descriptive analysis and quantitative analysis(average difference test) with primary data from the October-November 2019 survey. The analysis resultsconclude:The use of Google Classrom has good potential to support inexpensive and practical learning. LaaRooiba's IAI-N academic community generally has a good perception of the adoption of Google Classroomas an inexpensive and practical e-Learning model. The difference in campus location does not significantlyaffect the different perceptions of using cyberspace media in learning at IAI-N Laa Roiba. However, thereis a potential (standard error of 10%) that differences in location affect the perception of cognitive andaffective aspects. Faculty differences have a real impact on the perception of the application of GoogleClassroom in learning. The perception of the academic community of the Syriah faculty is relatively betterthan that of the tarbiyah faculty. Especially in the affective and conative aspects, but not significantlydifferent in cognitive aspects. The difference in age as a whole does not affect the change in perception ofthe study sample. But, partially, the age difference only has a significant impact on the conative aspect, noton the cognitive and affective aspects. Differences in student-teacher status differ only in significance inthe conative and total score aspects of the session. While in cognitive and affective aspects, students andlecturers did not differ significantly. Gender differences are correlated with differences in the perception ofthe adoption of Google Classroom at IAI-N Laa Roiba. Especially in cognitive and conative aspects.Significant affective aspects if the standard error is raised to 10%.Keywords: Cyberspace, Google Classroom, Inexpensive, Lecture, Practical